2016
DOI: 10.3103/s0096392516040118
|View full text |Cite
|
Sign up to set email alerts
|

Association between individual EEG characteristics and the level of intelligence

Abstract: The aim of the study was to investigate the relationship between individual characteristics the electroencephalogram in the resting state and the level of non-verbal intelligence. The study involved 77 students of Yaroslavl State University. Analyzing the relationship between IQ and spectral parameters of EEG theta, alpha and two sub bands of beta oscillations, we have found out that amplitude and power of alpha band EEG oscillations and low frequency beta bend EEG oscillations were positively correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This finding would have been overlooked and missed by the spectral analysis method. Stankova et al found that the degree of CD and intelligence level are positively correlated [17], and they concluded that the magnitude of CD is a measure of intelligence. Recorded EEG data suggested that participants with highly oscillating EEG have higher intelligence test scores than those with more periodic oscillations.…”
Section: Cognitionmentioning
confidence: 99%
“…This finding would have been overlooked and missed by the spectral analysis method. Stankova et al found that the degree of CD and intelligence level are positively correlated [17], and they concluded that the magnitude of CD is a measure of intelligence. Recorded EEG data suggested that participants with highly oscillating EEG have higher intelligence test scores than those with more periodic oscillations.…”
Section: Cognitionmentioning
confidence: 99%
“…However, acrossstudy findings on relations between individual differences in intelligence and intrinsic brain signal complexity are heterogeneous. Higher intelligence has been associated with higher complexity (Jaušovec and Jaušovec, 2003;Stankova and Myshkin, 2016;Thatcher et al, 2005), Dreszer et al (2020) found both positive and negative associations, and other studies could not find any significant relation (Anokhin et al, 1999;Ueno et al, 2015). Sample characteristics (Dreszer et al, 2020), varying complexity measures (Ferenets et al, 2006;Goldberger et al, 2002), and differences in the considered type of neural complexity, i.e., complexity that has been linked to local (short-range) vs. global (long-range) neural processing (Courtiol et al, 2016;Dreszer et al, 2020;Vakorin et al, 2011) were proposed as contributing to this heterogeneity.…”
Section: Introductionmentioning
confidence: 98%
“…However, acrossstudy findings on relations between individual differences in intelligence and intrinsic brain signal complexity are heterogeneous. Higher intelligence has been associated with higher complexity (Jaušovec and Jaušovec, 2003;Stankova and Myshkin, 2016;Thatcher et al, 2005), Dreszer et al (2020) found both positive and negative associations, and other studies could not find any significant relation (Anokhin et al, 1999;Ueno et al, 2015). Sample characteristics (Dreszer et al, 2020), varying complexity measures (Ferenets et al, 2006;Goldberger et al, 2002), and differences in the considered type of neural complexity, i.e., complexity that has been linked to local (short-range) vs. global (long-range) neural processing (Courtiol et al, 2016;Dreszer et al, 2020;Vakorin et al, 2011) were proposed as contributing to this heterogeneity.…”
Section: Introductionmentioning
confidence: 99%